Parental satisfaction with care given in neonatal intensive care units, multicentre referral hospitals in eastern Ethiopia - Workie Dagnew, Mekdes; Motuma, Aboma; Gebreyesus, Arsema; Shiferaw, Kasiye (Frontiers in Pediatrics, 2025)
BackgroundParental satisfaction is an important dimension of the quality of a child's care and has been shown to improve health outcomes, including adherence to therapeutic regimens and understanding of medical information. Parental satisfaction is low in resource-limited countries like Ethiopia, with the paucity of evidence. This study aimed to determine the magnitude of parental satisfaction with care given in neonatal intensive care and its associated factors among parents of neonates admitted to neonatal intensive care units (NICUs) at referral hospitals in eastern Ethiopia from June to August 2023.MethodA facility-based cross-sectional study was conducted among 418 parents whose new-borns were admitted to the NICU and who were selected using a systematic random sampling technique. A pretested semi structured questionnaire was used to collect the data through face-to-face interviews with participants, and a checklist was used to review the charts/records by trained and experienced bachelor nurse/midwife data collectors. The data were coded, entered into Epi-Data version 4.6, and transferred to SPSS version 25 for analysis. We used binary logistic regression analysis to identify factors associated with the outcome variable. An adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to report the findings, and a p-value ≤0.05 was considered to indicate statistical significance.ResultsThe magnitude of parental satisfaction with care given in the NICU was 50.5% (95% CI: 45.6–55.5). Being a rural resident (AOR = 2.13; 95% CI: 1.33–3.43), having a shorter hospital stay (AOR = 4.25, 95% CI: 2.08–8.69), being able to breastfeed (AOR = 2.46; 95% CI: 1.48–4.09), having a single birth (AOR = 4.16; 95% CI: 1.91–9.03), and the availability and quality of the family room (AOR = 2.36; 95% CI:1.40–3.99) were significantly independent associated factors with parental satisfaction with care given in the NICU.ConclusionOnly one in two parents were satisfied with the care given in the NICU. The present study highlights that shortening hospital stays, mothers' ability to breastfeed their newborns, having a single birth, and the availability and quality of the family room contribute to enhancing parental satisfaction with care given in the NICU in eastern Ethiopia.